IC 9424 Mobile Mine Equipment Maintenance Safety: A Review Of U.S. Bureau Of Mines Research - Joan K. Kuenzi (The National Institute for Occupational Safety and Health (NIOSH), 1995)
This Information Circular brings together for consideration recommendations from U.S. Bureau of Mines research in the area of surface mine mobile equipment maintenance for the period 1982 through 1991. It updates the 1982 contract report by Baker and Alves that formed the basis for much of the work described in the present report. Recommendations for hazard abatement during work on mobile one equipment are presented and stem from the results and recommendations of the research in two areas: (1) equipment and workplace hazard reduction, and (2) management of maintenance information. Recommendations included in this report apply to both the operators and maintainers of mobile mining equipment as well as to the manufacturers of that equipment.